PENGARUH SHOPPING LIFESTYLE DAN FASHION INVOLVEMENT TERHADAP IMPULSE BUYING PADA PELANGGAN SHOPEE: (Studi pada Mahasiswa ITS Khatulistiwa) - Elondri; Desda, Mia Muchia; Devi, Anita Sari (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2023)
This study aimed to explore the impact of shoppers' lifestyles and fashion involvement on impulse buying behavior among Shopee customers at ITS Khatulistiwa Pasaman Barat campus. The research involved 83 participants, all of whom were ITS Khatulistiwa students. The selection of participants followed a purposive sampling method, where specific criteria set by the researcher, including being Shopee users residing near the equator and having a history of making purchases, were used to identify suitable candidates. The findings of this study unveiled significant insights. Firstly, the Shopping Lifestyle variable exhibited a substantial positive influence on Impulse Buying among Shopee Customers, with a regression coefficient of 0.407 and a significance level of 0.000 (below 0.05). Secondly, the Fashion Involvement variable also displayed a noteworthy and statistically significant impact on Impulse Buying among Shopee customers, with a regression coefficient of 0.193 and a significance level of 0.000 (below 0.05). Notably, when both Shopping Lifestyle and Fashion Involvement were considered collectively, they collectively exerted a substantial positive and statistically significant influence on impulse buying behavior among Shopee customers, with a regression coefficient of 158.068 and a significance level of 0.000 (below 0.05), elucidating 79.8% of the observed variance. The remaining 20.2% was attributed to unexamined factors outside the scope of this study.